Resíduos eletroeletrônicos como tema de educação ambiental no ensino médio - Freitas, Marcelo Batista de (2018)
The present work is based on the elaboration and development of a didactic sequence in high school, focusing on the electro-electronic residues and the theme of Environmental Education, under the teaching approach CTSA (Science-Technology-Society-Environment). Its development in the school context was followed by research of a qualitative nature and with some quantitative contribution. The group involved was the 2nd year of the High School of a public elementary school in the city of Ituiutaba-MG and understood epistemic and pedagogical relations in a classroom of chemistry in the process of contextualization and construction of meanings. It was tried to articulate concepts of the discipline of Electrochemistry, to familiarize the students with materials that make up the electrical and electronic equipments and to make them aware of the issues arising from the inadequate disposal of electro-electronic waste, especially batteries and batteries. The didactic sequence, organized under the Three Pedagogical Moments (3MP) dynamics, and developed with new methodologies and interdisciplinary and contextualized activities, contributed significantly to construct meanings for studied concepts and bring about changes in the posture of each individual.